Value creation in mergers and acquisitions: The case of Portuguese banks - Pereira, Adalmiro (2020)
The main reason for mergers and acquisitions (M & A) that have occurred in the last twenty years, is the creation of value for shareholders and for the entity. Several authors have written on this topic and if everyone concludes that M & A should create value, in practice this may not be true. For this reason, it was pertinent to carry out this study, where the main objective is to verify if the M & A really create value or not, for the investors and organizations involved. The sample collected is based on some M & A registered in the Portuguese banking sector. In the first point, some of the strategic variables used by the banks involved in the transaction were identified. Then it was ascertained whether there was value creation or not in the banks involved in the M & A process. After the study was carried out, it was concluded that most of the mergers discussed in this study have created value and that there is no relation between strategic similarity and value creation.Taking into account our results, some suggestions for further work were mentioned.